2022
DOI: 10.1590/1678-6971/eramf220088
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of Corporate Governance on Pay-Performance Sensitivity: A New Perspective

Abstract: Purpose: This research investigates whether the characteristics of corporate governance (executive compensation, board composition, ownership structure, and control) influence the sensitivity of remuneration to firms’ performance, the so-called pay-performance sensitivity. Originality/value: This study brings to the literature a new perspective on the interaction of corporate governance mechanisms aligned with the concept of pay-performance sensitivity. The study shows that governance instruments are not isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 44 publications
3
7
2
Order By: Relevance
“…Ataay (2018) also found as the share ownership of blockholders increases, the sensitivity of executive COMP to CP decreases. Similar results were obtained by Iglesias et al (2022) for ownership concentration. An alternate explanation for these results could be the prevalence of family firms in India, where promoters own and control the firm.…”
Section: Analysis and Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Ataay (2018) also found as the share ownership of blockholders increases, the sensitivity of executive COMP to CP decreases. Similar results were obtained by Iglesias et al (2022) for ownership concentration. An alternate explanation for these results could be the prevalence of family firms in India, where promoters own and control the firm.…”
Section: Analysis and Findingssupporting
confidence: 88%
“…These results support the stewardship theory, which emphasizes the steward role of CEOs who align their interests with the shareholders, leading to wealth maximization (Patnaik and Suar, 2020). Iglesias et al (2022) also found a positive and significant impact of CEOD on the sensitivity of executive COMP to CP. Hence, H6(b) is rejected.…”
Section: Impact Of Board Characteristics On Chief Executive Officer C...supporting
confidence: 77%
“…Given the evidence that greater concentration leads to a more remarkable ability of shareholders to protect their interests (Conyon & He, 2011), studies demonstrate that governance mechanisms related to the control structure and the Board are capable of influencing executive remuneration, reflected in the value of companies (Iglesias et al, 2022).…”
Section: Board Ownership Concentration and Research Hypothesesmentioning
confidence: 99%
“…In general, studies evaluate the existence of a relationship between the level of remuneration and performance (see, for example, Aguiar & Pimentel, 2017;Degenhart et al, 2017;Ernel & Medeiros, 2020;Leite & Hein, 2019;Silva et al, 2018), as well as the sensitivity of executive remuneration to performance (see, for example, Brandão et al, 2019;Iglesias et al, 2022). This study differs from previous ones by treating determinants and investigating factors capable of affecting the portion of remuneration not explained by organizational performance, which may be disconnected from a direct contribution to shareholders, understood as an agency cost (Marquezan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The studies on PPS are inconclusive (Aguiar & Pimentel, 2017;Brandão et al, 2019;Ghrab et al, 2021;Iglesias et al, 2022;Iyengar & Sundararajan, 2021). In addition, studies on the impact of ESG disclosure on executive pay (Cai et al, 2011;Gillan et al, 2010;Jian & Lee, 2015;Karim et al, 2018;Rath et al, 2020) and the moderating effect of ESG disclosure on the sensitivity of executive pay to market performance (Chang et al, 2018;Cho & Ibrahim, 2021;Rath et al, 2020), a relationship that has not been identified in the national literature, are scarce and inconclusive from a theoretical and empirical point of view.…”
Section: Introductionmentioning
confidence: 99%